Detection of Trend in Hydrologic Variables Using Non-Parametric Test: A Study on Surma River in Northeastern Bangladesh - Islam, M. S.; Sikder, M. B. (Journal of Scientific Research, 2017)
An initiative has been taken to investigate the trends in discharge and water level (WL) of the Surma River in northeastern Bangladesh. The daily time series data of discharge and WL from two stations named Kanairghat and Sylhet with a period of 42 years (1973 2014) and 35 years (1980 2014) respectively have been analyzed. Non parametric Mann-Kendall Test has been applied to detect the trend and Sens slope estimator is used to measure the slope of the trends. In Kanairghat station, annual mean WL has significant trend (P: 0.03); while, annual mean discharge, mean monsoon discharge, annual maximum discharge, mean monsoon WL, and annual maximum WL shows insignificant trend (P: 0.24, 0.46, 0.14, 0.05, and 0.12). In Sylhet station, annual mean discharge, annual maximum discharge, and annual mean WL have significant trend (P: 0.03, 0.004, and 0.02). In other hand, mean monsoon discharge, mean monsoon WL, and annual maximum WL in Sylhet station has insignificant trend (P: 0.46, 0.13, and 0.21). According to Sens slope statistics, all of the detected trends, except annual maximum WL at Sylhet station, are downward. This study recommends a comprehensive water management scheme should be taken to ensure sustainable use of the river water.